REINSURANCE SERVICE AND ITS ECONOMIC NATURE - Ткаченко, К.; Свитайло, В. (SWorldJournal, 2021)
The main legislative and scientific-theoretical approaches to the definition of "reinsurance" are studied, as well as its legislative nature is revealed. Theoretical and applied approaches to clarifying the essence of reinsurance are analyzed. According t